Left Ventricular Function Changes Induced by Moderate Hypothermia Are Rapidly Reversed After Rewarming—A Clinical Study. Issue 1 (January 2022) - Wisløff-Aase, Kristin; Skulstad, Helge; Beitnes, Jan Otto; Lundblad, Runar; Halvorsen, Per Steinar; Fiane, Arnt; Espinoza, Andreas
Abstract : OBJECTIVES: Targeted temperature management (32–36°C) is used for neuroprotection in cardiac arrest survivors. The isolated effects of hypothermia on myocardial function, as used in clinical practice, remain unclear. Based on experimental results, we hypothesized that hypothermia would reversibly impair diastolic function with less tolerance to increased heart rate in patients with uninsulted hearts. DESIGN: Prospective clinical study, from June 2015 to May 2018. SETTING: Cardiothoracic surgery operation room, Oslo University Hospital. PATIENTS: Twenty patients with left ventricular ejection fraction greater than 55%, undergoing ascending aorta graft-replacement connected to cardiopulmonary bypass were included. INTERVENTIONS: Left ventricular function was assessed during reduced cardiopulmonary bypass support at 36°C, 32°C prior to graft-replacement, and at 36°C postsurgery. Electrocardiogram, hemodynamic, and echocardiographic recordings were made at spontaneous heart rate and 90 beats per minute at comparable loading conditions. MEASUREMENTS AND MAIN RESULTS: Hypothermia decreased spontaneous heart rate, and R-R interval was prolonged (862 ± 170 to 1, 156 ± 254 ms, p < 0.001). Although systolic and diastolic fractions of R-R interval were preserved (0.43 ± 0.07 and 0.57 ± 0.07), isovolumic relaxation time increased and diastolic filling time was shortened. Filling pattern changed from early to late filling. Systolic function was preserved with unchanged myocardial strain and stroke volume index, but cardiac index was reduced with maintained mixed venous oxygen saturation. At increased heart rate, systolic fraction exceeded diastolic fraction (0.53 ± 0.05 and 0.47 ± 0.05) with diastolic impairment. Strain and stroke volume index were reduced, the latter to 65% of stroke volume index at spontaneous heart rate. Cardiac index decreased, but mixed venous oxygen saturation was maintained. After rewarming, myocardial function was restored. CONCLUSIONS: In patients with normal left ventricular function, hypothermia impaired diastolic function. At increased heart rate, systolic function was subsequently reduced due to impeded filling. Changes in left ventricular function were rapidly reversed after rewarming. Abstract : Supplemental Digital Content is available in the text.